PENGUATAN PENDIDIKAN KARAKTER DALAM KEGIATAN KEPRAMUKAAN UNTUK MELATIH KEMANDIRIAN SISWA MADRASAH IBTIDAIYAH DI KECAMATAN TRAWAS - Misnan Misnan (Universitas Trilogi, 2020)
The purpose of this study was to analyze scouting activities as strengthening character education for students of Madrasah Ibtidaiyah (MI) in training independence and to describe scouting activities as strengthening character education for MI students in training independence. Scouting activities as a strengthening of character education in students are very necessary, because with character education students can become strong individuals so that they are able to ward off bad influences in the environment where they live, as well as in training students' independence. The obstacle faced is the packaging of activities. The packaging of activities needs to be thought about so that it looks attractive and elegant so that students are not bored, as well as the availability of sufficient funds for the development of activities and support from parents to achieve maximum results.